Concept and Classification of Covert Embezzlement of the Property of Another - O. V. Haidar (Bulletin of Kharkiv National University of Internal Affairs)
The author has studied the concept of covert embezzlement of the property of another, which is provided by the legislator and has analyzed the concepts revealed by leading scholars in the field of criminal law and in the field of criminalistics. The peculiarities inherent in theft in contrast to other lucrative criminal offenses have been highlighted. The statistical data for 2020 provided by the Office of the Prosecutor General regarding registered thefts on the territory of Ukraine have been analyzed. A statistical comparison of registered thefts with other lucrative criminal offenses and with all registered criminal offenses has been conducted.